A Study on Patient Complaint Management in Hospitals Affiliated to Kashan University of Medical Sciences and Approaches for Improvement - Fatemeh Rangraz Jeddi; Azam Haj Mohammad Hosseini; Mehdi Shaeri (Patient Safety and Quality Improvement Journal, 2016)
Introduction: Complaint is the expression of dissatisfaction with an organization in relation to its products or services. The aim of this study was to investigate the complaint management process in hospitals affiliated to Kashan University of Medical Sciences and to propose solutions for the improvement of this process. Materials and Methods: This cross-sectional, applied study was performed in 2013 at all hospitals affiliated to Kashan University of Medical Sciences, Kashan, Iran. The study was conducted in two major steps, i.e., evaluation of the process and solution delivery. The study population in the evaluation step comprised of 27 individuals who were involved in the complaint management process. On the other hand, 40 experts were recruited in the second stage. Sample selection was performed through targeted random sampling. Data were collected, using a checklist which was based on the national and international standards. The checklist, consisting of 101 yes/no questions was completed via interview and observation. Also, the expert comments were collected through Delphi technique. For statistical analysis, descriptive statistics were calculated, using SPSS Version 16. Results: Based on the findings, 8 (29.6%) out of 27 participants stated that patients had access to information related to the process of complaint registration.  All 27 (100%) participants claimed that no committees at hospitals were responsible for investigating patient complaints, although the patients could completely track their complaints. Conclusion: Based on the findings, there was inadequate information regarding the process of patient complaint management in the evaluated hospitals.